2015
DOI: 10.1039/c5tc02219c
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and thermal transport properties of spark plasma sintered n-type Bi2Te3−xSex alloys: the combined effect of point defect and Se content

Abstract: Performance enhancement can be realized in p-type Bi 2 Te 3 but hardly in n-type Se-modified Bi 2 Te 3 alloys fabricated by powder processing as compared with conventional ingots. To reveal the reasons and investigate the optimal Se content in fine-grained n-type Bi 2 Te 3Àx Se x materials processed by mechanical alloying (MA) and spark plasma sintering (SPS), the amount of Se was varied in a wide range and electrical transport properties were investigated and discussed in association with the results of Hall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(83 citation statements)
references
References 33 publications
4
76
0
3
Order By: Relevance
“…19,20 Our group has already confirmed that Bi 2 Te 2.2 Se 0.8 is the optimal composition for samples prepared by MA and SPS. 21 Bi 2 Te 3 is anisotropic with a layered structure composed of a quintuple atomic series in the order of Te(1)-Bi-Te(2)-Bi-Te(1) along the c-axis. Their electrical and thermal conductivities along the a-axis (in the c-plane) are approximately four and two times higher, respectively, than those along the c-axis of Bi 2 Te 3 .…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Our group has already confirmed that Bi 2 Te 2.2 Se 0.8 is the optimal composition for samples prepared by MA and SPS. 21 Bi 2 Te 3 is anisotropic with a layered structure composed of a quintuple atomic series in the order of Te(1)-Bi-Te(2)-Bi-Te(1) along the c-axis. Their electrical and thermal conductivities along the a-axis (in the c-plane) are approximately four and two times higher, respectively, than those along the c-axis of Bi 2 Te 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the goal of upshifting the service temperature in this work is translated into how to conduct intrinsic point defect engineering via extrinsic Sb and In doping. 13,[32][33][34] Intrinsic point defects are primarily entropic defects. They are thermally more robust than extrinsic point defects and therefore favor robust high-temperature performance.…”
Section: Introductionmentioning
confidence: 99%
“…Hence an electronic semiconductor exhibiting conduction switching can be a good choice for application. Chalcogenide such as bismuth telluride based alloys are electronic semiconductor and they are extensively used as conventional thermoelectric material for converting waste heat into electrical energy in the temperature range of ≤300 °C . Bismuth telluride is a V–VI chalcogenide compounds with narrow band gap semiconductor of 0.16–0.3 eV .…”
Section: Comparison Of the Elemental Composition Obtained By Xps And mentioning
confidence: 99%
“…Chalcogenide such as bismuth telluride based alloys are electronic semiconductor and they are extensively used as conventional thermoelectric material for converting waste heat into electrical energy in the temperature range of ≤300 °C . Bismuth telluride is a V–VI chalcogenide compounds with narrow band gap semiconductor of 0.16–0.3 eV . It has a hexagonal lattice type in space group R3¯m, and in its structure Te and Bi atomic layers arranged in the order of –Te(1)–Bi–Te(2)–Bi–Te(1)– in the quintpule layer along the c axis direction.…”
Section: Comparison Of the Elemental Composition Obtained By Xps And mentioning
confidence: 99%
See 1 more Smart Citation